(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2012)
Strength behavior of water saturated subsidented soils is studied. A linear dependence of relative subsidence deformation of compacting stresses while σz<Psl,0, becoming to power dependence when σz>Psl,0 is found out experimentally. In conditions of water saturation the shear resistance chart represents a broken line, which vertex corresponds to the initial subsidence value. Necessity to determine the shear resistance arguments for each compacting stress σz>Psl,0 on reverse branch of compression curves on Nichiporovich method is established.